Chương I - Căn bậc hai. Căn bậc ba

NC

Chứng minh

\(\frac{2\left(\sqrt{3}-1\right)}{4-2\sqrt{3}+1}=\frac{6\sqrt{3}+2}{13}\)

H24
30 tháng 7 2019 lúc 21:01

Cái này dễ mà, nhân lượng liên hợp là ra thui :v

Ta có

\(VT=\frac{2\left(\sqrt{3}-1\right)}{4-2\sqrt{3}+1}=\frac{2\sqrt{3}-2}{5-2\sqrt{3}}\\ =\frac{\left(2\sqrt{3}-2\right)\left(5+2\sqrt{3}\right)}{\left(5-2\sqrt{3}\right)\left(5+2\sqrt{3}\right)}\\ =\frac{10\sqrt{3}+\left(2\sqrt{3}\right)^2-10-4\sqrt{3}}{5^2-\left(2\sqrt{3}\right)^2}\\ =\frac{6\sqrt{3}+12-10}{25-12}\\ =\frac{6\sqrt{3}+2}{13}=VP\left(đpcm\right)\)

Bình luận (0)

Các câu hỏi tương tự
DQ
Xem chi tiết
TL
Xem chi tiết
HT
Xem chi tiết
H24
Xem chi tiết
LN
Xem chi tiết
HN
Xem chi tiết
HL
Xem chi tiết
H24
Xem chi tiết
GV
Xem chi tiết